127 Standardising Access to Fracture Fixation Simulation for Core Surgical Trainees. (4th May 2021) - Brown, R; Curwen, C; Mutimer, J
Abstract: Introduction: Simulation is increasingly being used to augment clinical experience. However, access to simulation varies geographically and national courses can be costly. The Severn School of Surgery aimed to provide a locally run, cost-neutral "Basic Principles in Fracture Fixation" course to standardise access to simulation for core surgical trainees (CSTs). Method: The course ran from a district general hospital, accommodating lectures, case discussions, and practical stations (screw fixation, plate fixation, dynamic hip screw, and external fixation). Faculty donated their time and a devices company provided kit and dry bones. CSTs organised the course. Pre- and post-course self-rated Intercollegiate Surgical Curriculum Programme (ISCP) global competency ratings in the practical stations were recorded and usefulness of aspects of the course was recorded. Results: 32 candidates attended. Mean self-rated competency increased by at least one global rating in all practical stations (p < 0.05). All aspects of the course were deemed useful (pre-course reading by 27/28, lectures by 31/32, and case discussions by 31/32). No net cost was incurred. Conclusions: Increases in self-rated competency in surgical skills can be obtained through a cost-neutral, trainee-organised, regional skills course. Pre-course reading, lectures, case discussions, and practical sessions are all useful. This model can be used by others to standardise the simulation curriculum.